Simple tools to monitor the anoxic condition of wastewater based on MFCs reversal signals. (March 2023) - Tucci, Matteo; Espinoza-Tofalos, Anna; Barontini, Enrico; Formicola, Francesca; Bonelli, Paolo; Franzetti, Andrea; Papacchini, Maddalena; Cristiani, Pierangela
Highlights: Plate and cylindrical MFCs with different carbon electrodes operated on site. Reversal of MFCs signal indicated scarcely of the anoxic condition of wastewater. Protozoa of Euglyphida Order grazing the anode of planar MFC were documented. MFCs scarcely correlated with chemical-physical parameters than with anoxic conditions. Abstract: Microbial fuel cells have been proposed as possible alternative method to monitor organic content and other parameters of wastewaters. However, still rare, and short in-field experimentations were completed. In this work, long-term tests with two types of microbial fuel cells (planar and tubular geometry), equipped with carbon electrodes differently enriched and doped (enriched with carbon Nanotube, Ce-doped and/or undoped), were carried out in a wastewater plant (Bresso, Italy) aiming at the monitoring of the anoxic process in the tank. This experimentation aimed to improve experiences previously collected in different wastewater plants in Italy. Physico-chemical (temperature, light, redox potential) parameters were monitored during the MFCs' operations. A hand-made automatic water sampler was used to perform some punctual chemical (COD, N, oxygen) measurements. The results indicated variable anoxic conditions in the monitored wastewater. The presence of a rich flora of protozoa on the anodes confirmed this condition. The MFCs signal was consequently very low during seasons of the year. Cathode and anode reversed, having different microbial activity on the anode and on the cathode. Next Generation Sequencing (NGS) of S16 RNA analysis gave insight on bacteria pools and the type of biofilm developing on different anodes and cathodes of MFCs.